Chapter 1 How open borders can unlock cultures Concepts, methods, and procedures - Leggio, Daniele Viktor (Taylor & Francis, 2018)
In March 2014, the e-mail list of the European Academic Network on Romani Studies1 hosted a discussion on definitions of the population known as 'Roma'. It began when one of the subscribers to the list - which at the time brought together some 350 academics who specialised in Romani/Gypsy studies - asked for reactions to two generalisations which she came across while preparing a legal review of a document on cultural rights: (1) that all Roma speak a variety of the same language, Romanes; and (2) that Roma generally consider themselves to be a nation. Some two-dozen scholars posted their reactions, which together offer a fairly exhaustive summary of contemporary views on the subject